The Relative Contribution of Causal Attribution and Academic Procrastination to Future Anxiety Among University Students Expected to Graduate - Albarjas, Khawlah Khalifah (Dirasat: Human and Social Sciences, 2026)
Objectives: This study aimed to identify the predictive ability of causal attribution and academic procrastination on future anxiety among students expected to graduate from Al-Jouf University, Saudi Arabia. Method: A descriptive methodology was employed, utilizing scales for causal attribution, academic procrastination, and future anxiety. The study sample included 480 male and female students expected to graduate. Results: The findings revealed a statistically significant negative correlation between causal attributions (internal stable, internal unstable, and external stable) and future anxiety, while a positive correlation emerged between external unstable attributions and academic procrastination with future anxiety. Furthermore, most dimensions of causal attributions and academic procrastination were predictive of future anxiety. Specifically, the coefficient of determination for internal unstable attributions, external stable attributions, external unstable attributions, and academic procrastination were 7%, 3%, 24%, and 32%, respectively. However, internal stable attributions did not significantly predict future anxiety. Additionally, external unstable causal attributions varied by gender, favoring males. Conclusion: Based on the results, the study recommends leveraging the dimensions of causal attribution and academic procrastination to develop interventions aimed at reducing future anxiety among prospective graduates.